Designing for fires in the UK can we learn from the NIST report? : delegate information, Monday 27th March 2006. (Thomas Telford, 2006)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held on 27 March 2006.